Intervention strategies to enhance food safety certification adoption among farmers in Malaysia: A system dynamics approach - Mohd Shahir, Omar; Cheng, Jack Kie; Ahmad Afif, Ahmarofi; Muhammad Fakhrul, Yusuf (Learning Gate, 2024)
This study aims to identify the key elements influencing the adoption of food safety certification in Malaysia's agricultural industry. By analysing elements derived from past studies conducted between 2018 and 2023, expert agreement on these elements was obtained using the Fuzzy Delphi Method. Simulation modelling further examined these elements to identify the primary influencing elements and propose intervention strategies. Based on insights from 30 experts in the agriculture industry with over five years of experience in Malaysia, out of 33 identified elements, only 22 elements influence the adoption as influencing the adoption of food safety certification. A simulation model using system dynamics was used to test the agreed element. From these findings, 11 Causal Loop Diagrams were developed. Using the Causal Loop Diagram, a stock and flow analysis simulation model were created to test the elements affecting the adoption of food safety certification. Two of the five elements tested were identified as critical factors requiring attention for adopting food safety certification: awareness campaigns and enforcement. The findings of this research will offer significant insights to stakeholders, facilitating the improvement of current policy strategies to effectively encourage the adoption of food safety certification among farmers in Malaysia.